Counsellor Bias in Occupational Choice for Female Students - Kahn, Sharon E.; Schroeder, Alana S. (Canadian Journal of Counselling and Psychotherapy, 2012)
To investigate counsellor bias in occupational choice for female students, six short case studies were employed that could describe either a male or a female. Two hundred randomly selected school counsellors in British Columbia were asked to select three appropriate occupations for each case subject. When the case study described a female, the counsellors chose occupations that paid less and were more closely supervised than when the same case study described a male.